Land Consolidation as a Cause of Agrarian Conflict in Maluku (2008-2017): The Role of the GPM in Advocating for the Rights of Indigenous Peoples - Wutres, Sadrak L.; Luturmas, Jochbeth D. (West Science Social and Humanities Studies, 2025)
Land consolidation is a land management policy that aims to improve land efficiency and productivity. However, in Maluku, this policy often causes agrarian conflicts due to discrepancies between regulations, government interests, and the rights of indigenous peoples. One notable case is the agrarian conflict in the Aru Islands, where the granting of land concessions to PT Menara Group without the consent of indigenous communities sparked widespread resistance. The Protestant Church of Maluku (GPM) plays an important role in advocating for the rights of indigenous communities through the #SaveAru alliance and various environmental advocacy policies. This study uses a qualitative approach with a case study method to analyze land consolidation policies, socio-economic impacts, and the role of GPM in advocating for the rights of indigenous communities in Maluku. The results of the study show that weak regulations and the neglect of indigenous peoples' rights have contributed to the failure of land consolidation, leading to prolonged agrarian conflicts. Therefore, stricter regulations and the active role of civil society, including religious institutions, are needed to oversee equitable agrarian policies.